Repurposing of nervous system drugs for cancer treatment: recent advances, challenges, and future perspectives - Zixun Wang; Chen Xu; Qi Wang; Yudong Wang (Discover Oncology)
Abstract The nervous system plays a critical role in developmental biology and oncology, influencing processes from ontogeny to the complex dynamics of cancer progression. Interactions between the nervous system and cancer significantly affect oncogenesis, tumor growth, invasion, metastasis, treatment resistance, inflammation that promotes tumors, and the immune response. A comprehensive understanding of the signal transduction pathways involved in cancer biology is essential for devising effective anti-cancer strategies and overcoming resistance to existing therapies. Recent advances in cancer neuroscience promise to establish a new cornerstone of cancer therapy. Repurposing drugs originally developed for modulating nerve signal transduction represent a promising approach to target oncogenic signaling pathways in cancer treatment. This review endeavors to investigate the potential of repurposing neurological drugs, which target neurotransmitters and neural pathways, for oncological applications. In this context, it aims to bridge the interdisciplinary gap between neurology, psychiatry, internal medicine, and oncology. By leveraging already approved drugs, researchers can utilize existing extensive safety and efficacy data, thereby reducing both the time and financial resources necessary for the development of new cancer therapies. This strategy not only promises to enhance patient outcomes but also to expand the array of available treatments, thereby enriching the therapeutic landscape in oncology.